Art, the Ancient Spirit of ‘Gotong Royong’, and The Global Pandemic Village - Salima Hakim (Graduate School of Institut Seni Indonesia Yogyakarta, 2021)
AbstractAccording to the World Giving Index, a study done by the Charities Aid Foundation that provides insights into the global trends of generosity, Indonesia has taken the top position of the chart and was named 2020’s most charitable country in the world. The notion of communality, consensus and collectivity, also known in Javanese as gotong royong or mutual assistance, a prominent characteristic associated with the traditional village life, appeared to also transpire within the global village. As we are universally connected through the digital world and are collectively experiencing a global pandemic where all art activities came to a halt, it is important to look further into how art adapted to these sudden changes and limitations of circumstances. Using a cultural studies approach and virtual ethnography data collecting, this paper will seek to examine how several online art initiatives try to embody the spirit of collectivity, using artworks as a tool of activism to help others survive the pandemic and at the same time reimagining the notion of gotong royong that can persist in the digital village that functions as a form of collective belonging to the concept of a nation. Aktivitas Seni sebagai Medium Gotong Royong di Era PandemiAbstrakMenurut World Giving Index, sebuah studi yang dilakukan oleh the Charities Aid Foundation yang memberikan wawasan tentang tren global kedermawanan, Indonesia menempati posisi teratas dan dinobatkan sebagai negara paling dermawan tahun 2020 di dunia. Gagasan komunalitas, konsensus dan kolektivitas, yang juga dikenal dalam bahasa Jawa sebagai gotong royong, karakteristik yang diasosiasikan dengan tradisi dan kehidupan wilayah desa, tampak juga terjadi di dalam desa virtual. Karena kita terhubung secara universal melalui dunia digital dan secara kolektif sedang mengalami pandemi global di mana semua kegiatan seni terhenti, penting untuk melihat lebih jauh bagaimana seni beradaptasi dengan perubahan dan keterbatasan keadaan yang terjadi. Dengan menggunakan pendekatan kajian budaya dan pengumpulan data etnografi virtual, makalah ini akan mencoba mengkaji bagaimana beberapa inisiatif seni daring mencoba untuk mewujudkan semangat kolektivitas, menggunakan karya seni sebagai alat aktivisme yang dapat membantu orang lain dalam kondisi pandemi, dan di saat yang sama kembali membayangkan gagasan gotong royong di desa digital sebagai usaha untuk menjadi bagian dari konsep sebuah bangsa.